2015
DOI: 10.1177/1358863x14564592
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative prophylaxis of venous thromboembolism (VTE) in patients undergoing high ligation and stripping of the great saphenous vein (GSV)

Abstract: To analyze the necessity of venous thromboembolism (VTE) prophylaxis for patients undergoing high ligation and stripping of the great saphenous vein (GSV) and to estimate the efficacy and safety of different anticoagulant protocols in a single-center randomized controlled trial with large sample size. A total of 2196 patients undergoing high ligation and stripping of the GSV were randomized to one of the following postoperative VTE prophylaxis protocols: group A, no VTE prophylaxis (n=542); group B, subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The incidence of haemorrhagic complications was gener-ally low in each group but was higher in group B (0.75%) compared to the other groups. The authors concluded that postoperative VTE thromboprophylaxis following high ligation and GSV stripping effectively reduces venous thrombosis complications [60]. In another prospective randomised study, 48 women received LMWH prophylaxis two days after surgery and 45 women received LMWH within seven days of surgery [61].…”
Section: Venous Thromboembolism Prophylaxis After Varicose Vein Surgementioning
confidence: 99%
“…The incidence of haemorrhagic complications was gener-ally low in each group but was higher in group B (0.75%) compared to the other groups. The authors concluded that postoperative VTE thromboprophylaxis following high ligation and GSV stripping effectively reduces venous thrombosis complications [60]. In another prospective randomised study, 48 women received LMWH prophylaxis two days after surgery and 45 women received LMWH within seven days of surgery [61].…”
Section: Venous Thromboembolism Prophylaxis After Varicose Vein Surgementioning
confidence: 99%
“…Wang et al, in a study on DVT prophylaxis in venous surgery reported a 5.17% of DVT and 1.48% of pulmonary embolism, a non-negligible percentage for benign disease. 27 Chen et al found an incidence of postoperative DVT in stripping of 7.7%, higher than expected. 28 Bukina and Golovlev, in stripping with “miniflebectomy” on local anesthesia, detected a crural DVT in 3.5% of cases.…”
Section: Discussionmentioning
confidence: 81%
“…23 ) In addition, Wang et al also reported that postoperative DVT occurred in 20 cases (5.17%) among 542 cases of stripping surgery in patients with GSV incompetence, and that 67.9% of the DVT cases were found within 2 weeks after the surgery. 24 ) These results highlight that it may not be possible to detect worsening of IDDVT if it happens 1–2 weeks after VV surgery. Therefore, this study did not completely clarify whether or not the IDDVT changed (or worsened) postoperatively.…”
Section: Discussionmentioning
confidence: 90%